Ecologia e biologia populacional dos ermitões (Decapoda, Anomura) do litoral norte de Santa Catarina - Stanski, Gilson [UNESP] (2015)
The increase in the fishing fleet in southern Brazil has contributed to decrease in landings of profitable shrimps and bycatch species. The aim of this study is to investigate the biodiversity and spatial-temporal distribution of anomuran crustaceans captured as bycatch in the non-selective fishery of shrimps on the northern coast of Santa Catarina state, Brazil. In addition, we analyzed the influence of environmental factors on the abundance patterns of studied species. Monthly trawls were conducted in Babitonga Bay from July 2010 through June 2011, using a shrimp boat outfitted with double-rig nets, at depths from 5 to 17 m. Ecological indices (species richness, diversity, dominance and evenness) and redundancy analysis were assessed to analyze the hermit community and their relation with environmental factors. A total of 647 individuals were collected, represented by three families, six genera and seven species. Isocheles sawayai showed the highest abundance, flowed by Loxopagurus loxocheles. Both species demonstrated a positive correlation with temperature and phi (smaller sediment grain size). The highest richness and the evenness value were estimated at the depth 17 m. Otherwise, the five meters deep has the lowest evenness because the high dominance of I. sawayai, resulting in a lower estimated diversity. In a period with lower temperature and higher salinity as July were registered higher levels of diversity, probably because the lower dominance of tropical species (I. sawayai) and the occupation of species distributed in offshore regions (Petrochirus diogenes, Dardanus insignis, Pagurus exilis). Thus, the capture effort designated in the shrimp fishery carried an important diversity of anomuran crustaceans and others animal species, showing a danger to the marine trophic web